Coupled Simulation of Ice-Structure Interaction of Offshore Wind Turbines in Bhawc Using Vanilla - Willems, Tom (author); Hendrikse, H. (author) (2019)
Offshore wind turbines at locations where sea or lake ice is present need to be designed to withstand ice-induced loading. For vertical-sided support structures, such as monopiles, the effects of ice-induced vibrations need to be considered in the design. Current practice is either to use approaches provided in design standards, or for example to apply pre-generated ice load time series in the wind turbine aeroelastic model. These approaches have the drawback that the coupling between ice failure behavior and structural motion is not included. The effect of omitting this coupling on predictions for fatigue and ultimate limit states is currently not known. To enable fully coupled simulations in the design of offshore wind turbines, an existing simulation model for ice crushing has been recently coupled (“VANILLA”) to the in-house aeroelastic software package BHawC. In this paper this fully coupled model is applied to simulate ultimate limit state design load cases (DLCs) for a recent design of an offshore wind turbine on a monopile foundation. The project that is chosen for this case study is situated in the Southern Baltic Sea. The loads obtained for ice- and wind loading with the VANILLA model are compared to wind- and wave-induced loading. It is found that intermittent crushing is the governing ice interaction mode for offshore wind turbine support structures and rotor-nacelle-assembly components. Offshore Engineering